(untitled) - Greene, William H. (Boston, 2012)
For first-year graduate courses in Econometrics for Social Scientists. This title is a Pearson Global Edition. The Editorial team at Pearson has worked closely with educators around the world to include content which is especially relevant to students outside the United States. This text serves as a bridge between an introduction to the field of econometrics and the professional literature for graduate students in the social sciences, focusing on applied econometrics and theoretical concepts.
Thống kê kinh tế xã hội nâng cao,Kinh tế lượng nâng cao,Kinh tế lượng
Keywords: Kinh tế lượng,Econometrics